PENGARUH DIMENSI LINGKUNGAN DAN KEPUASAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA PERUMDA ANEKA USAHA SEGER JOMBANG - Putri, Rany Renzindia Alma; Halima, Nur; Suindiyah D., Sayekti (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This research aims to analyze the influence of the work environment and job satisfaction on employee performance, either directly or indirectly, with motivation as an intervening variable. The method in this research is a quantitative approach with a sample of 52 respondents. The data analysis technique uses Partial Least Square (PLS) based on Structural Equation Model (SEM) version 4.0. The research results show that the work environment and job satisfaction have a direct effect on employee performance at Perumda Aneka Usaha Seger Jombang; Motivation directly has an influence on employee performance at Perumda Aneka Usaha Seger Jombang; and Motivation partially mediates the relationship between Work Environment and Job Satisfaction on Employee Performance at Perumda Aneka Usaha Seger Jombang.